EXECUTIVE FUNCTIONING IN PATIENTS WITH ALCOHOL DEPENDENCE BEFORE AND AFTER MEDITATIVE PRACTICES - Singh, Ankita; Khess, C.R. J; Lahiri, Deyashini (International Journal of Psychosocial Rehabilitation, 2020)
There is asignificant need for research regarding the impact of meditative practices on executive functioning. The present study conducted to see the effect of meditative practices on executive functioning. Executive functioning is related to the higher cognitive functioning of the brain which includes attention, problem solving ability, abstract reasoning as well as its ability to organize information to working memory. As we know who have a dependence on alcohol shown impairment in a wide array of executive functioning such as problem solving, verbal fluency, cognitive flexibility, information sequencing and working memory. It tends to affect the quality of life and occupational functioning. In most of the studies found that meditation has a positive effect on the executive functioning such as making planning, attentional capacity and enhance cognitive flexibility.  This study assessed the effect of meditation on executive functioning in patients with alcohol dependence. This study comprised20 alcohol patients, in whom 10 patients belonged to an experimental group and 10 patients belonged to treatment as usual group. After the initial screening by the clinical assessment based on their amenability for the interview, a tool for the executive functioning (Wisconsin Card Sorting Test) applied to the patients. Experimental group of patients received one week meditation but treatment as usual group did not receive any therapy. After one week again both group assessed on the tool of executive functioning (Wisconsin Card Sorting Test). This study found that meditation has a positive effect on executive functioning.